Pengembangan Media Pembelajaran Berbasis Adobe Animate Pada Tema Makanan Di Sekelilingku Untuk Menumbuhkan Minat Belajar Siswa SMP/MTs: Pengembangan Media Pembelajaran - Khoirotunnisa, Nisa; Nulhakim, Lukman; Taufik, Annisa Novianti (UNIB Press, 2026)
Interest in learning is one of the crucial elements in science learning. Based on interviews conducted by researchers, students' interest in learning is still relatively low because the learning media used are less interesting and boring and the learning methods used tend to be monotonous. One solution that can be taken to foster interest in learning is by developing Adobe Animate-based learning media. The purpose of this study is to analyze the level of product validity and the level of readability test of Adobe Animate-based learning media with the theme of food around me in fostering learning interest in junior high school/Islamic junior high school students. The research method used is Research and Development (R&D) according to Borg and Gall which is modified according to the needs of researchers which is limited to the design validation stage until product revision. The instruments used are assessment sheets for media experts, material experts and practitioners as well as readability test sheets. The study was conducted in 2 junior high schools and 1 Islamic junior high school in Cilegon City. Data were analyzed quantitatively and qualitatively. The validation results showed that this learning media obtained a score of 90.45% with a